Effect of dissolved Si on the corrosion of iron in deaerated and slightly alkaline solutions (pH ≈ 8.1) at 50 °C. (January 2023) - Galai, Leila; Marchetti, Loïc; Miserque, Frédéric; Frugier, Pierre; Godon, Nicole; Brackx, Emmanuelle; Remazeilles, Céline; Refait, Philippe
Abstract: Corrosion of iron in deaerated and slightly alkaline buffered solutions was investigated for different Si concentrations ([Si] varying from ≈0 to ≈110 mg L −1 ) over a ≈ 30 days period. In these solutions, iron corrosion led to the formation of a layer consisting of a mixture of Fe oxides and Fe silicates on the metal surface, but also to the precipitation of the same compounds in the medium and to the release of Fe cations. An increase in [Si] promoted the formation of Fe silicates at the expense of Fe oxides, but without increasing the total amount of iron corroded. Highlights: Fe corrosion in Si alkaline solution leads to Fe oxide and Fe silicate formation. An increase in [Si] promotes Fe silicate formation at the expense of Fe oxide. An increase in [Si] causes no enhancement of iron corrosion.